KONSEP DAN IMPLEMENTASI PRINSIP HALAL DALAM KEUANGAN DAN PERBANKAN SYARIAH SERTA PERAN FATWA DAN DEWAN PENGAWAS SYARIAH - Livia Safitri; Salsa Bila; Lisnawati Lisnawati (JURNAL ILMIAH NUSANTARA, 2026)
The development of Islamic finance demands the application of halal principles that are not only understood conceptually, but also implemented in banking practice. This article aims to examine the concept of halal principles in Islamic finance and how they are implemented in the operational activities of Islamic banks. The method employed is a literature study, reviewing various sources such as books, journals, and relevant regulations. Halal principles in Islamic finance are grounded in the prohibition of riba (usury), gharar (uncertainty), and maisir (speculation), while emphasizing the values of justice, transparency, and maslahah (public interest) in every transaction.The implementation of these halal principles is reflected in the various products and services offered by Islamic banks, which utilize contracts (akad) in accordance with Sharia law. Furthermore, the existence of fatwas and the Sharia Supervisory Board (Dewan Pengawas Syariah/DPS) plays a pivotal role in ensuring that all banking activities remain compliant with Sharia provisions. The DPS is responsible for supervising, providing guidance, and ensuring Sharia compliance in the operations of financial institutions. Accordingly, the interrelationship between concept, implementation, and supervision constitutes the primary factor in maintaining the integrity of and public trust in the Islamic financial system.